The Wicked Character of Psychosocial Risks: Implications for Regulation - Jespersen, Anne Helbo; Hasle, Peter; Nielsen, Klaus T. (Nordic Journal of Working Life Studies, 2016)
Psychosocial risks constitute a significant problem in most workplaces, and they are generally considered more difficult to regulate than many other occupational health and safety risks. This article investigates the challenges of regulating psychosocial risks in the workplace. The difficulties lie in the particular nature of psychosocial risks: their complexity, uncertainty, value, and power divergences. Psychosocial risks therefore resemble ‘wicked problems’, typically characterized by unclear cause-effect relationships and uncertain solutions. We use the ‘wicked problems’ concept to show how workplace regulation, and particularly the enforcement in the form of inspection and audits of certified occupational health and safety management systems, face challenges in assessing psychosocial risks and the strategies used by regulators to overcome these challenges. While regulation has become more effective in several countries, a better understanding of the nature of the challenges is still needed. It is necessary to accept the uncertain nature of psychosocial risks in the search for more efficient regulation. Achieving more effective regulation should involve stakeholders in the workplace who deal with the prerogatives of management, and should help develop the competencies of the inspectors and auditors in the field.